Chagas Heart Failure in Patients from Latin America - Bestetti, Reinaldo B (Card Fail Rev, 2016)
Physicians working in Europe and the United States should suspect Chagas heart failure in every patient coming from Latin America with chronic heart failure. Diagnosis should be confirmed by positive serology. Right bundle branch block and left anterior fascicular block on 12-lead electrocardiogram, enlarged cardiac silhouette with no pulmonary congestion on chest X-ray and left ventricular apical aneurysm on echocardiography are the distinctive features of this condition. The clinical course is poorer than that of non-Chagas heart failure; however, medical treatment is similar. Implantable cardioverter-defibrillators are useful in the primary and secondary prevention of sudden cardiac death. Cardiac resynchronisation therapy can be given to patients on optimal medical therapy and with lengthened QRS complex. Heart transplantation is the treatment of choice for patients with end-stage Chagas heart failure.